Prioritizing patients for hip fracture surgery: the role of frailty and cardiac risk - Forssten, Maximilian Peter; Mohammad Ismail, Ahmad; Ioannidis, Ioannis; Ribeiro, Marcelo A. F.; Cao, Yang; Sarani, Babak; Mohseni, Shahin (Frontiers in Surgery, 2024)
Introduction: The number of patients with hip fractures continues to rise as the average age of the population increases. Optimizing outcomes in this cohort is predicated in timely operative repair. The aim of this study was to determine if patients with hip fractures who are frail or have a higher cardiac risk suffer from an increased risk of in-hospital mortality when surgery is postponed >24 hours. Methods: All patients registered in the 2013-2021 TQIP dataset who were ≥65 years old and underwent surgical fixation of an isolated hip fracture caused by a ground-level fall were included. Adjustment for confounding was performed using inverse probability weighting (IPW) while stratifying for frailty with the Orthopedic Frailty Score (OFS) and cardiac risk using the Revised Cardiac Risk Index (RCRI). The outcome was presented as the absolute risk difference in in-hospital mortality. Results: A total of 254,400 patients were included. After IPW, all confounders were balanced. A delay in surgery was associated with an increased risk of in-hospital mortality across all strata, and, as the degree of frailty and cardiac risk increased, so too did the risk of mortality. In patients with OFS ≥4, delaying surgery >24 hours was associated with a 2.33 percentage point increase in the absolute mortality rate (95% CI: 0.57-4.09, p=0.010), resulting in a number needed to harm (NNH) of 43. Furthermore, the absolute risk of mortality increased by 4.65 percentage points in patients with RCRI ≥4 who had their surgery delayed >24 hours (95% CI: 0.90-8.40, p=0.015), resulting in a NNH of 22. For patients with OFS 0 and RCRI 0, the NNHs were 345 and 333, respectively. Conclusion: Delaying surgery beyond 24 hours from admission increases the risk of mortality for all geriatric hip fracture patients. The magnitude of the negative impact increases with the patient's level of cardiac risk and frailty. Operative intervention should not be delayed based on frailty or cardiac risk.